Discontinuation of empirical antibiotic therapy in neutropenic acute myeloid leukaemia patients with fever of unknown origin: is it ethical?. (9th December 2013) - Micol, J.‐B.; Chahine, C.; Woerther, P.‐L.; Ghez, D.; Netzer, F.; Dufour, C.; Merad, M.; Blot, F.; Chachaty, E.; de Botton, S.; Gachot, B.; Grobusch, M.
Abstract Based on recommendations of the ECIL‐4, we prospectively evaluated discontinuation of empirical antibiotic therapy in high‐risk neutropenic acute myeloid leukaemia patients with fever of unknown origin. Seven patients (median neutropenia duration 30 days) were included. Four of them remained afebrile but quickly recovered from neutropenia. The other three had rapid recurrent fever. Two of these three patients had bacteraemia with susceptible strains and one of them was transferred to the ICU for septic shock. Median duration of sparing of antibiotics for the seven patients was 3 days (2–4). Because of these limited results the study was stopped.